Madrasah Religious Culture on Students' Religious Moderation Attitude: Quantitative Correlation at MAN 1 Jombang - Ashoumi, Hilyah; Rofi’ah, Lutfi Inayatur; Sabilah, Fatimah Nilda (PALAPA, 2024)
This study aims to determine the effect of madrasah religious culture on students' religious moderation attitudes at MAN 1 Jombang. This research is a correlational quantitative research with the type of ex post facto non-experimental research. The population and samples in this study were tenth grade students of MIPA MAN 1 Jombang, which amounted to four hundred populations with one hundred students as research samples. Data collection using a questionnaire, and data analysis using simple regression analysis techniques. This study concluded that the religious culture of madrasah has a significant influence on the religious moderation attitude of MAN 1 Jombang students, as evidenced by the Sig = 0.01 < α = 0.05 value. The correlation coefficient value r square = 0.946 or contributes 94.6%.